2003
DOI: 10.1021/ma021795s
|View full text |Cite
|
Sign up to set email alerts
|

Physically Controlled Radical Polymerization of Vaporized Vinyl Monomers on Surfaces. Synthesis of Block Copolymers of Methyl Methacrylate and Styrene with a Conventional Free Radical Initiator

Abstract: Physically controlled radical polymerization of vinyl monomers with conventional free radical initiators was achieved in the presence of monomer vapors on solid substrate surfaces. The polymerization of methyl methacrylate (MMA) and styrene (St) by 2,2‘-azobis(isobutyronitrile) (AIBN) on substrate surfaces resulted in the deposition of high molecular weight polymers, forming a rough surface morphology in such forms of aggregated particles. The proportional relationship between the number-average molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…Endo and coworkers reported physically controlled radical polymerization of vapor-phase vinyl monomers by conventional free-radical initiators deposited onto solid surfaces, such as aluminum plate. [76][77][78][79] Deposition polymerization in monomer vapor of MMA and styrene was initiated from free radicals on the surface and high molecular weight polymers formed on the substrate surfaces. During polymerization, the number-average molecular weight was found to increase linearly with polymer yield.…”
Section: Discussionmentioning
confidence: 99%
“…Endo and coworkers reported physically controlled radical polymerization of vapor-phase vinyl monomers by conventional free-radical initiators deposited onto solid surfaces, such as aluminum plate. [76][77][78][79] Deposition polymerization in monomer vapor of MMA and styrene was initiated from free radicals on the surface and high molecular weight polymers formed on the substrate surfaces. During polymerization, the number-average molecular weight was found to increase linearly with polymer yield.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the propagation reaction was greatly accelerated once the reaction time exceeded 5 h. A similar phenomenon was observed in a previous study of VASP. 10 Thus, this acceleration must be caused by factors such as an increase in the adsorption and absorption area of monomer molecules and the suppression of termination reactions caused by the isolation of active chain ends on the top surface of deposits, as reported previously. 11 Multimodal profiles with wide polydispersity values are typical profiles of the photo-VASP products obtained in this study.…”
Section: Resultsmentioning
confidence: 72%
“…14 The molecular weight of the extracted polymers ranged from 28 600 to 1 160 000 in M w , with large polydispersity values of 2.6-4.9, consistent with the peculiar structural property of photo-VASP products as previously reported. 10,12,15 As listed in Table 1, PFMA production with HMPP gradually increased from 2.7 to 7.5 mg over a period of up to 5 h. Over 5 h, a significant increase in polymer accumulation (410.8 mg) was observed as shown in samples 1-5 (reaction time 6 h), with an extreme increase in molecular weight. This suggests that the propagation reaction was greatly accelerated once the reaction time exceeded 5 h. A similar phenomenon was observed in a previous study of VASP.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…It was also revealed that, because of a particular interaction between silicate platelet surfaces and MMA units in copolymer chains, a small number of MMA units in a styrene-MMA copolymer induced the exfoliation of layered silicates [30]. Considering the easy preparation of block copolymers and other advantageous features of VASP method [31], various designs of polymer structure by VASP could be created on the silicate layer surfaces to prepare nanocomposites that maintain their structures after melt processing.…”
Section: Introductionmentioning
confidence: 99%